FROM THE HISTORY OF TURKIC KHAJIBS WHO SERVED THE SAMANIDS: ALPTEGIN - Abdukamolova Moxlaroy Shuxratjon qizi (Sciental Journals Publishing, 2025)
The 9th–10th centuries mark a period of significant political and military transformations in Central Asia. One notable aspect of this era was the rise of Turkic commanders who served under the Samanid dynasty and gradually emerged as powerful political actors. Among them, Alptegin stands out for having risen through the ranks as a military slave (ghulam) and later establishing an autonomous political authority in Ghazna. This article explores Alptegin’s career, his relations with the Samanids, his conquest of Ghazna, and his role in laying the foundation of the Ghaznavid state. Drawing on key historical sources such as Tarikh-i Bayhaqi, Zayn al-Akhbar, Tarikh-i Yamini, and Siyasatnama, this paper highlights the transformation of military slaves into political elites in early Islamic Central Asia.
Keywords: Alptegin, Samanids, Ghazna, Ghaznavids, ghulam, political elite, 9th–10th century, Central Asia, Transoxiana, Khurasan, Balkh, Siyasatnama, Tarikh-i Bayhaqi, Tarikh-i Yamini, Zayn al-Akhbar, military slavery, Turkic commanders, hajib, sipahsalar, independent rule, Islamic statecraft, court officials, medieval generals.